2011
DOI: 10.1186/1475-2875-10-357
|View full text |Cite
|
Sign up to set email alerts
|

Free distribution of insecticidal bed nets improves possession and preferential use by households and is equitable: findings from two cross-sectional surveys in thirteen malaria endemic districts of Bangladesh

Abstract: BackgroundBRAC, an indigenous non-governmental development organization (NGO), has been implementing a programme to prevent and control malaria in the 13 malaria-endemic districts of Bangladesh since 2007. One of the critical preventive interventions is the distribution of insecticidal bed nets (long-lasting insecticide-treated nets, LLINs and insecticide-treated ordinary nets, ITNs) to the community free of cost. This study aimed to assess progress in the possession, preferential use, and knowledge on use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 20 publications
5
37
1
Order By: Relevance
“…These results are also consistent with other reports on bed net use in the Chittagong Hill Districts, which have reported high-bed net use in the area. 23,24 Another possible mechanism that was consistent with the results of this study is that lack of access to care may contribute to higher infection rates in jhum cultivators. Qualitative results found that jhum cultivators delayed treatment until the symptoms became severe because of the distance of jhum sites to the village and perceived need to stay at jhum sites and continue cultivation.…”
Section: Discussionsupporting
confidence: 80%
“…These results are also consistent with other reports on bed net use in the Chittagong Hill Districts, which have reported high-bed net use in the area. 23,24 Another possible mechanism that was consistent with the results of this study is that lack of access to care may contribute to higher infection rates in jhum cultivators. Qualitative results found that jhum cultivators delayed treatment until the symptoms became severe because of the distance of jhum sites to the village and perceived need to stay at jhum sites and continue cultivation.…”
Section: Discussionsupporting
confidence: 80%
“…Although NGOs were supposed to distribute ITNs to every family [14] of the study area some respondents claimed that they had yet to receive any form of bed net (ITNS or LLINS). Many respondents mentioned that a household would receive a single net but this was not sufficient for all of their family members.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the current malaria control strategy in Bangladesh relies mainly on the use of ITNs/LLINs. For several years, this strategy has benefited from a mass campaign promotion [14]. Before the introduction of treated nets, Bangladesh reported as about 50,000 confirmed malaria cases and 450 malaria deaths annually [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Laos, for example, community members including village health volunteers help to carry ITNs from the healthcare facility to the community and to distribute them among households [10]. A similar community-based net distribution system is in place in many countries including Bangladesh, Vietnam, Kenya and Nigeria [1114]. …”
Section: Introductionmentioning
confidence: 99%